DAMPAK PENGUNAAN INTERAKSI GAME ONLINE TERHADAP KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI SURABAYA - Rossa Ragil Pangestuti; Wulan Patria Saroinsong; Suharti; Muhammad Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the impact of online game interaction on the social- emotional abilities of 5-6 year old children in Surabaya using a quantitative approach and ex post facto method. The respondents in this study were the biological mothers of 5-6 year old children who were considered to have emotional closeness and adequate understanding of their children's social-emotional conditions. Data were collected through questionnaires designed based on the dimensions of online game interaction use and children's social- emotional abilities, then analyzed using simple linear regression with the help of the SPSS program. The results showed that the use of online game interactions had a significant negative impact on the social-emotional abilities of 5-6 year old children in Surabaya, as indicated by a decline in social interaction, cooperation, empathy, and control of children's emotions and behavior. Based on these results, it can be concluded that the higher the intensity of online game interaction usage, the greater the potential for hindering the social- emotional development of early childhood, thus requiring the role of parents and educators in supervising and directing online game usage so that it does not have a negative impact on children's development.